A Study of the Relationship between Ambient Lead and Blood Bead among Gasoline-Station Workers - AR Bahrami; H Mahjub; MJ Assari (Tehran University of Medical Sciences, 2002)
Consumption of leaded gasoline in Iran cause to emit lead compounds in ambient air of gasoline stations and is known to effect on workers health in these locations. The objectives of this study were assessment of ambient lead levels and blood lead levels of gasoline station workers in Hamadan city, Iran. For this purpose, 82 samples were obtained in ambient air of gasoline station locations. Serum samples from 44 workers and 44 unexposed people were collected to determine blood lead levels. Samples were analyzed with atomic absorption spectrometry. Blood lead levels in workers and control group were 30.05 and 17.31 µg/dl, respectively. The correlation coefficient between blood lead level and ambient lead level, age as well as duration of employment were 0.44, 0.66 and 0.81, correspondingly. The highest concentration of lead was recorded at the gasoline station in the city center. A high correlation between vehicle numbers in gasoline station locations and lead concentration was determined in the city center, but with a poor correlation in the suburb of the city. 48% of exposed workers had blood lead levels more than the biological exposure limit recommended by American Conference of Governmental Industrial Hygiene (ACGIH). Using unleaded gasoline and liquefied gas together with a health program education are importance factors to reduce blood lead level in workers of gasoline stations.